BEST PRACTICE: DIGITALIZATION, PUBLIC SERVICE AND COMMUNITY SATISFACTION AT SAMSAT BANTEN - Mohammad Hasbyel Fahmi; Rizky Ilhami (SEAN Institute, 2023)
Digitalization has become an integral part of the public service system, particularly in the realm of motor vehicle tax services. This process necessitates a comprehensive understanding of taxpayers' attitudes and responses towards utilizing the digital tax payment system. The objective of this research is to analyze the best practices in the integrated public service of Samsat in Banten. The research methodology employed is qualitative, utilizing a purposive sample comprising individuals from the community who have utilized the public service both online and offline. Data collection techniques include interviews, observational studies, and documentation, with the researcher serving as the primary instrument for data gathering. The data analysis involves interactive interpretation. The research findings indicate that the successful implementation of a digital service system necessitates continuous support, including a thorough comprehension of the public's attitudes and behaviors in their interaction with digital services. Digitalization significantly enhances the quality of Samsat's public services in Banten. Conversely, the system must be reinforced by a socialized policy framework that motivates taxpayers. A deeper understanding of digital governance systems in tax payments would be more effective with the support of an understanding of the existing technology cohort within society.